Biochemical and genetic analysis of butyrylcholinesterase (BChE) in a family, due to prolonged neuromuscular blockade after the use of succinylcholine - Garcia, Daniel Fantozzi (Sociedade Brasileira de Genética, 2011)
Butyrylcholinesterase (BChE) is a plasma enzyme that catalyzes the hydrolysis of choline esters, including the muscle-relaxant succinylcholine and mivacurium. Patients who present sustained neuromuscular blockade after using succinylcholine usually carry BChE variants with reduced enzyme activity or an acquired BChE deficiency. We report here the molecular basis of the BCHE gene underlying the slow catabolism of succinylcholine in a patient who underwent endoscopic nasal surgery. We measured the enzyme activity of BChE and extracted genomic DNA in order to study the promoter region and all exons of the BCHE gene of the patient, her parents and siblings. PCR products were sequenced and compared with reference sequences from GenBank. We detected that the patient and one of her brothers have two homozygous mutations: nt1615 GCA > ACA (Ala539Thr), responsible for the K variant, and nt209 GAT > GGT (Asp70Gly), which produces the atypical variant A. Her parents and two of her brothers were found to be heterozygous for the AK allele, and another brother is homozygous for the normal allele. Sequence analysis of exon 1 including 5′UTR showed that the proband and her brother are homozygous for –116GG. The AK/AK genotype is considered the most frequent in hereditary hypocholinesterasemia (44%). This work demonstrates the importance of defining the phenotype and genotype of the BCHE gene in patients who are subjected to neuromuscular block by succinylcholine, because of the risk of prolonged neuromuscular paralysis.